Differences in estimation of sugarcane phenotypic parameters using unmanned aerial vehicle multispectral and hyperspectral data - Chen Yanli; Huang Lu; Yang Shaoe; Sun Ming; Ding Meihua; Huang Lining; Ma Ruisheng; Liang Chi; Yang Xin; Chen Cheng (Computers and Electronics in Agriculture, 2026)

Tensile behavior and failure mechanisms of multi-bolt sleeved joints in pultruded multi-directional FRP square tubes with constraint effects - Leizhi Zhang; Xin Wang; Jingyang Zhou; Lining Ding; Jialin Liu; Zhishen Wu (Engineering Structures, 2026)

Elucidating the molecular mechanisms underlying nicosulfuron degradation by Serratia sp. NS8 through multi-omics analysis - Kuo Liu; Yulin Wu; Yubo Ding; Yufeng Xiao; Lining Zheng; Donghui Liu; Hao Zhang (Journal of Hazardous Materials, 2026)

Sugarcane Phenotypic Parameters Modeling Using Unmanned Aerial Vehicle Multispectral Data - Yanli Chen; Lu Huang; Mingzhi Li; Ming Sun; Meihua Ding; Lining Huang; Ruisheng Ma; Chi Liang; Xin Yang; Cheng Chen (Sugar Tech, 2026)

Connection behavior and failure mechanisms of FRP sleeved joints with bonded inserts versus conventional bolted joints - Leizhi Zhang; Xin Wang; Lining Ding; Jingyang Zhou; Jialin Liu; Zhishen Wu (Engineering Structures, 2026)

Investigation of Turbulence Intensity Effects on Tidal Turbine Wakes Through the BEM–CFD Method - Erhu Hou; Yang Li; Lining Zhu; Yanan Wu; Jie Ding; He Wu (Journal of Marine Science and Engineering, 2025)
The wake characteristics of tidal turbines are significantly influenced by turbulence intensity (TI) and flow velocity in the marine environment. This study employs the Blade Element Momentum (BEM)–CFD method to model two-bladed horizontal tidal turbine wakes, simplifying the turbine geometry while ensuring computational efficiency. The numerical model, validated against experimental data, demonstrates reliable accuracy. Simulations were conducted for background TI levels of 2%, 6%, 10%, 14%, and 18%. Results indicate that wake regions initially expand and then contract, with the contraction point moving closer to the turbine as TI increases. At 2% TI, the wake influence region extends to an axial distance/diameter (X/D) ratio of 20, while at 18% TI, contraction begins at X/D = 4. Low TI results in more extensive low-speed regions, whereas high TI accelerates wake recovery. As TI increases, the wake’s turbulence rapidly blends with the background, leading to a reduction in turbulence increments within the wake. Additionally, an analytical wake model for tidal turbines was developed, incorporating turbulence intensity into the formula. The predicted curve exhibited good agreement with the CFD data. This model enables a quick and efficient prediction of wake velocity changes under varying turbulence intensities.

Fatigue behavior of sleeved bolted joints with bonded inserts in pultruded FRP profile - Leizhi Zhang; Xin Wang; Lining Ding; Jialin Liu; Jingyang Zhou; Xing Wei; Zhishen Wu (Engineering Structures, 2025)

Biocontrol mechanism of strain DB02 against watermelon wilt and damping-off diseases caused by Fusarium oxysporum f. sp. niveum and Rhizoctonia solani - Yubo Ding; Hongyu Pan; Yan Wang; Lining Zheng; Hao Zhang (Food Bioscience, 2025)

Experimental study on the interfacial shear performance between macro basalt fibers reinforced UHPC as repair material and normal concrete - Zhiyuan Chen; Xin Wang; Lining Ding; Kaidi Jiang; Fusheng Niu; Hua Wang; Zhishen Wu (Engineering Structures, 2025)

Experimental and analytical investigation on the flexural behavior of FRP bars reinforced composite beams with an ultra-high performance seawater sea-sand concrete permanent formworks - Kaidi Jiang; Xin Wang; Lining Ding; Shui Liu; J.Y. Richard Liew; Jingyang Zhou; Yahia M.S. Ali; Zhishen Wu (Engineering Structures, 2025)

Improving synergistic catalysis of CuOx/AgOy/TiO2 for promoting selective catalytic oxidation of ammonia - Junfei Chen; Zhihao Yu; Jinwei Wu; Zhao-Bin Ding; Lin Lang; Lining Fang; Xiuli Yin; Zebao Rui (Chemical Engineering Journal, 2025)

Bond behavior of BFRP bars in ultra-high performance seawater sea-sand concrete reinforced by non-metallic fibers - Kaidi Jiang; Xin Wang; Qingguo Ben; Lining Ding; Zhiyuan Chen; J.Y. Richard Liew; Hongjian Du; Zhishen Wu (Engineering Structures, 2024)

Experimental and numerical investigations of the effects of various tensile reinforcement types on the structural behavior of concrete bridge deck slabs - Yahia M.S. Ali; Xin Wang; Lining Ding; Shui Liu; Zhishen Wu (Engineering Structures, 2023)

Dynamic equity carbon permit allocation scheme to limit global warming to two degrees - Lining Wang; Wenying Chen; Hongjun Zhang; Ding Ma (Mitigation and Adaptation Strategies for Global Change, 2017)